Kinematic and electromiographic analysis of the water polo crawl while leading the ball: A pilot study - Pereira, F.; Figueiredo, P.; Goncalves, P.; Pereira, S.; Vilas-Boas, J. P.; Fernandes, R. J.; Machado, L. (The Open Sports Sciences Journal, 2010)
Our aim was to conduct a kinematic and electromyographic characterization of the water polo front crawl while leading the ball technique. A high level male water polo player performed an experimental protocol of 3x15m at front crawl while leading the ball (with rest intervals of 2min between repetitions). Each repetition was performed in acceleration. One complete stroke cycle was analyzed for each repetition of 15m using surface electromyography to analyse the bíceps femoris, gastrocnemius medialis, tricips brachii, bíceps brachii, deltoideus posterior and rectus femoris muscles. The protocol was also recorded by 2 surface and 4 underwater cameras in order to assess centre of mass (CM) velocity during the cycle and its fluctuations. EMG signal was digital filtered (35-500Hz), full-wave rectified, calculated the linear envelope, normalized to the maximal isometric voluntary contraction and integrated (iEMG). The fluctuations of CM velocity were assessed though the coefficient of variation of the instantaneous velocity. Results showed that tricips brachii and gastrocnemius medialis were the most active muscles in the beginning of the cycle and that gastrocnemius medialis, deltoideus posterior and tricips brachii displayed the highest values (and bíceps brachii the lower values) of maximum electric activity and iEMG. It was observed an increase in the velocity of the CM at the beginning of the cycle, decreasing slightly afterwards, implying a reduced coefficient of variation (16.8). It should be evidenced the different involvement of the studied muscles in the cycle of front crawl while leading the ball and the consequent differences in the CM velocity.